Sistem Informasi Penyewaan Lapangan Futsal Menggunakan Metode First Come First Served Pada NF Mini Soccer: Futsal field Rental Information System Using The First Come First Served Method in NF Mini Soccer - Wulandari, Wulandari; Muhamad Resya Novario; Muhamad Fahreza (DRPM Universitas Budi Luhur, 2021)
At this time health is very important for our bodies, exercise is an option to keep the body in shape, one of the most popular sports is futsal. NF Mini Soccer is a business entity engaged in field rental services which is located at Jl. Saidi Raya No 9A Petukangan Selatan, Pesanggrahan, South Jakarta City and has been established since 2010. The problem with NF mini Soccer is that the mini soccer field rental process still uses written records, so there is no reminder that the schedule has been filled by another team, often there were clashes between teams and there was no information on the vacant field schedule. From these problems NF Mini Soccer needs to be made a system that can record the administration of futsal field rentals. So it is hoped that from better recording it will not disappoint customers/teams and can compete with other futsal field rentals..